MODERN APPROACHES AND INNOVATIONS IN TEACHING ENGLISH IN PRIMARY CLASSES - Boqiyeva Marjona Shuhratovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
In this article, as a result of the use of modern approaches and innovative methods in teaching English in primary grades, the development of students' logical thinking skills, fluency in speech, the formation of the ability to quickly and correctly answer, instilling enthusiasm for knowledge, information is given about the effort to prepare thoroughly for classes.